Administration Strategies for Innovative Organization of Medium-sized Primary Schools under the Office of the Basic Education Commission in the Northeastern Region - Yuwarachoth, Puridar; Bangwiset, Suchat; Nuntee, Sakdinaporn (Arts of Management Journal, 2024)
The objectives of this study were to 1) study components of innovative organizations. 2) to identify the current conditions, desirable conditions, and priority need index; 2) to create and develop strategies and the strategic manual; 3) to experiment with strategies and strategic manuals, and 4) to assess the quality of strategies and certify their strategic manuals. Use mixed-methods research. The research was divided into four phases. Phase 1: Study of innovative organizations using documentary study. Phase 2 investigated the priority need index, comprising with SWOT analysis with 17 stakeholders and a survey study sample group of 361 schools. Phase 3: construct the strategies comprising a multi-case study. Phase 4: construct the strategies comprising a multi-cases study. The research instruments were strategy assessment forms. Quantitative data were analyzed by mean standard deviations, and the priority index of essential needs, and qualitative data analysis through descriptive analysis. The findings of this study were summarized as follows: 1. The components of an innovative organization include 1) creating a vision for creative innovation challenges; 2) innovative organizational structure; 3) an innovative teacher team; 4) innovative behavior of teachers; and 5) school innovation culture. 2. The overall current condition and desirable level were at the highest level. The top three modified indexes were: 1) creating a vision and challenge 2) innovative organizational structure and 3) supporting the school’s innovative culture. 3. There were strategies as well as their strategy manuals: 1) vision; 2) mission; 3) goals 4) strategic planning 5) setting the strategy, including (1) creating a vision of innovation challenges. (2) designing an innovative organizational structure (3) promoting and developing innovative teacher teams; (4) promoting innovative behavior among teachers; and (5) promoting the school’s innovative culture. 4. The experimental group schools that were implemented developed into a very innovative organization -90.90 percent. The overall score was at its highest level. The propriety, feasibility, and utility were at the highest level.